2016
DOI: 10.2217/pgs.16.21
|View full text |Cite
|
Sign up to set email alerts
|

Common Genetic Variants in Platelet Surface Receptors and its Association with Ischemic Stroke

Abstract: Ischemic stroke has been named one of the leading causes of death worldwide. Whereas numerous biological mechanisms and molecules were found to be associated with stroke, platelets are particularly contributive to its pathogenesis. Recent data indicate considerable variability in platelet phenotype which accounts for differences in platelet surface receptor function, count and reactivity. These features collectively influence both the events leading to a disease and effectiveness of antiplatelet therapies. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…That study was consistent with the decrease in the platelet alpha-granule marker, transforming growth factor beta 1 after clopidogrel treatment, and the correlation between the effects of clopidogrel on BDNF and transforming growth factor beta 1 concentrations but not those after ASA treatment. In our previous studies, in a cohort of patients with type 2 diabetes, we found that platelet reactivity could be related to a number of clinical factors, biochemical variables and genetic polymorphisms (21,22,24,(37)(38)(39)(40)(41). Moreover, it was found that genetic polymorphisms within genes related to platelet reactivity could also be useful prognostic tools (42).…”
Section: Discussionmentioning
confidence: 97%
“…That study was consistent with the decrease in the platelet alpha-granule marker, transforming growth factor beta 1 after clopidogrel treatment, and the correlation between the effects of clopidogrel on BDNF and transforming growth factor beta 1 concentrations but not those after ASA treatment. In our previous studies, in a cohort of patients with type 2 diabetes, we found that platelet reactivity could be related to a number of clinical factors, biochemical variables and genetic polymorphisms (21,22,24,(37)(38)(39)(40)(41). Moreover, it was found that genetic polymorphisms within genes related to platelet reactivity could also be useful prognostic tools (42).…”
Section: Discussionmentioning
confidence: 97%
“…25 The remaining nonsynonymous variants (rs1654416, rs2304167, and rs1671152) are associated with amino acid substitutions: Lys237Glu, Thr249Ala, and His322Asn. 26 We and others showed independently that these variants are in linkage disequilibrium and create minor haplotypes at protein level with protein residues PEAN (in successive order: rs1613662, rs1654416, rs2304167, and rs1671152). 27 Three of these SNPs (rs1613662, rs1654416, and rs2304167) are localized in the extracellular topological protein domain.…”
Section: Discussionmentioning
confidence: 97%
“…Platelets have an important role in the pathogenesis of LVIS based on their activation and adherence to the Increased burden of rare deleterious variants of the KCNQ1 gene in patients with large-vessel ischemic stroke endothelium within cerebral arteries, as well as progression of thrombus (9,10). Most research strategies to date revealed the effect of genetic variation on reactivity of platelets and were obtained by analyzing common variants within candidate genes and/or genome-wide association studies (GWAS), followed by in vitro studies to assess platelet functions (11). Overall, previous studies on the genetic background of platelet reactivity indicated that many different genes contribute to platelet function.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, previous studies on the genetic background of platelet reactivity indicated that many different genes contribute to platelet function. Thus far, the potential contribution of genetic variants within genes encoding proteins essential to thrombus formation in LVIS have been analyzed in a small number of studies and the majority of them focused on the common single nucleotide polymorphisms (SNPs) within a few genes associated with glycoproteins on the platelet surface (11). The results of these studies suggested that additional loci associated with platelet functions are yet to be found and that the known loci may contain high effect rare risk variants that have thus far gone undetected by GWAS.…”
Section: Introductionmentioning
confidence: 99%